F-actin contractile rings in protoplasts of the yeast Schizosaccharomyces - Jochová, J; Rupes, I; Streiblová, E (Cell biology international reports, 1991)
By rhodamine-phalloidin fluorescence, distinct continuous F-actin rings were visualized in 18-20% of the protoplasts of Schizosaccharomyces pombe and S. japonicus var. versatilis, in addition to randomly distributed F-actin dots. Whereas the reversion of ring-lacking protoplasts coincided with the polarization of the dotted F-actin pattern, the ring-containing protoplasts became furrowed as the F-actin rings constricted. The furrowing was more conspicuous in S. japonicus var. versatilis than in S. pombe protoplasts and it was blocked when the reversion was inhibited by Novozyme 234 indicating that the cell wall formation is essential for the F-actin ring constriction.
Keywords: aktiny; Protoplasts; Species Specificity; protoplasty; Actins; buněčná stěna; cytoskelet; Schizosaccharomyces; druhová specificita; Cytoskeleton; Cell Wall